2019
DOI: 10.3390/agronomy9080412
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Increases the Physiological and Biochemical Stability of Soybean Plants under High Temperature

Abstract: Thermal stress reduces plant growth and development, resulting in considerable economic losses in crops such as soybeans. Nitric oxide (NO) in plants is associated with tolerance to various abiotic stresses. Nevertheless, there are few studies of the range of observed effects of NO in modulating physiological and metabolic functions in soybean plants under high temperature. In the present study, we investigated the effects of sodium nitroprusside (SNP, NO donor), on anatomical, physiological, biochemical, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
2
2
0
1
Order By: Relevance
“…The findings of our study also confirmed the beneficial effects of hydrogen sulfide and nitric oxide under salinity stress. These results are confirmed by the findings of Vital et al [16] according to them nitric oxide regulated the organic acid and amino acids of soybean plants under high temperature.…”
Section: Root Organic Acid Contentsupporting
confidence: 86%
“…The findings of our study also confirmed the beneficial effects of hydrogen sulfide and nitric oxide under salinity stress. These results are confirmed by the findings of Vital et al [16] according to them nitric oxide regulated the organic acid and amino acids of soybean plants under high temperature.…”
Section: Root Organic Acid Contentsupporting
confidence: 86%
“…This enzyme acts on the decomposition of H 2 O 2 , using it as an acceptor of electrons from the oxidation of phenolic compounds (Jóźwiak & Politycka, 2019). Vital et al (2019) found, in an experiment with the same soybean cultivar as in this study, an increase in POX activity, however, due to high temperature stress. Taken together, the photoprotective role of the antioxidant system of soybean plants stands out, due mainly to the HI condition, as evidenced by the greater activity of CAT, APX, SOD, and POX, without reduction of A .…”
Section: Discussionsupporting
confidence: 59%
“…Application of SNP resulted in the alleviation of high temperature stress-induced effects on net photosynthesis and maximal PSII photochemical efficiency. In several species such as chryasanthemum [ 76 ], soybean [ 17 ], rice [ 69 ], Lablab purpureus [ 63 ], and Festuca arundinacea [ 77 ], high temperature stress-induced decrease in photosynthesis alleviated by SNP treatment has been reported. In the present study, the activity of Rubisco was severely affected by the exposure to high temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…Application of sodium nitroprusside (SNP; NO source) has been found to stimulate activity of superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), and peroxidase (POD) under high temperature (45 °C) in reed plant callus and played an important role in the metabolism of H 2 O 2 [ 16 ]. While high temperature stress disturbs membrane thermo-stability and increases lipid peroxidation and electrolyte leakage in plants due to heat-induced oxidative burst [ 17 ], NO interacts with superoxide and hydroperoxyl radicals to act as a barrier and terminate their chain formation and ensure the protection of the membrane [ 18 ]. Several studies have shown that NO counteracts abiotic stress strongly by regulating sulfur (S)-assimilation [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%